PENGATURAN HUKUM PENYELESAIAN PERKARA MELALUI AKTA VANDADING (STUDI PUTUSAN No. 8/PDT.G/2018 PN TANJUNGBALAI) - Bahmid Bahmid; Irda Pratiwi; Ayu Wandira Marpaung (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2020)
Peace occurs when the parties that have made a joint agreement one of them does not carry out an achievement that has been agreed as outlined in a memorandum of agreement made in writing or not in writing. If the achievement is harmed by one of the parties by not implementing an achievement then a default arises. . Default arises when the parties violate a provision of 1320 BW which is the main condition for the occurrence of an agreement and carry out a form of achievement. In this paper using a normative juridical research method that takes a case approach in it. The issue raised by the author is How to Regulate the Peace of Debt Based on the Applicable Law and How the Application of the Peace of Debt through the Vandading Deed (Decision Study No. 8 / Pdt.G / 2018 / PN Tanjungbalai). In this study it can be concluded that in settling accounts receivable debts can be mediated and the court can settle peace through the Vandading deed.